Analytic method of structural analysis of modular buildings. Issue 1 (March 2020) - Shirokov, V S; Gordeeva, T E; Bocharov, A Yu
Abstract: The paper presents an analytical method of modular buildings calculation. It focuses upon basic design assumptions that are accepted for modular buildings calculation. The authors introduce their classification of loads and impacts, which are basic for modular buildings. They also describe a method of determining inertial forces from seismic action designed on the basis of a cantilever analytical model. Analytical and numerical methods for determining the forces in the elements of modular units are further compared. It is revealed that the analytical method strongly agrees with FEM (that is the finite elements method) with the error being 2-6%. The analytical method is sufficiently accurate for engineering calculations.